The crisis and renaissance of curriculum studies: A reflection on the Positions of Wraga and Hlebowitsh - Mulugeta Yayeh Worku (College of education, Bahir Dar University, 2023)
This article is mainly a reaction paper that reflects on the views and positions of Wraga and Hlebowitsh (2003) concerning the crisis and renaissance of the curriculum field. In doing so, a brief critical review of the two authors' views with regard to the ups and downs that the curriculum field has passed through, and most importantly, the crisis it faced as it went through its formative period was made. The article also endeavored to show the efforts of different curriculum scholars, including the proposals of these two authors, to rescue the field from its total collapse. Next to this, my reflections on the views and positions of the two authors vis-à-vis the current state of the field and the proposals they presented to solve its crisis are highlighted. The paper also tried to reflect on the current state of the Ethiopian curriculum field based on some personal experiences and observations. Accordingly, it revealed that many of the signs of curriculum crisis are prevalent in contemporary Ethiopia. Finally, concluding remarks and lessons to be learned from this article are included